Balancing the Benefits to Agriculture and Adverse Ecotoxicological Impacts of Inorganic Nanoparticles - de Sousa, Bruno Teixeira; de Oliveira, Jhones Luiz [UNESP]; Caixeta Oliveira, Halley; de Castro, Vera Lúcia S. S. (Springer Nature, 2022)
Nutrient fertilization and use of pesticides in agriculture aid in the improvement of crop productivity and quality. However, their use may be harmful to environmental health. It is then needed an innovative alternative in agricultural cultivation, increasing fertilizers and pesticides’ effectiveness, reducing its environmental impact, and improving food production. In particular, nanotechnology is emerging as a promising alternative. Inorganic nanoparticles can be used in association with active organic ingredients or as active ingredients. While nanofertilizers offer benefits in nutrition management, nanopesticides can increase environmental safety achieving better pest control. To that end, this chapter presents an overview of these materials’ use and their beneficial and damage effects in relation to conventional compounds. It describes the main types of nanofertilizers and nanopesticides (such as nanoparticles of essential elements and polymeric nanoparticles containing these elements), giving examples of products and their applications in plants compared to conventional chemicals. In contrast, despite the advantages of using nanotechnology in agriculture, it is necessary to consider its limitations and understand its environmental behavior. The internalization and subsequent toxicity of inorganic nanoparticles in the environment depend on their physical–chemical characteristics. It is essential to understand the biological responses to their exposure in nontarget organisms at various trophic levels, which may pose a risk to human health. In conclusion, although use of inorganic nanoparticles in agriculture offer opportunities to improve crop yields, it is mandatory to make a risk prognosis due to their use before their market entrance to make decisions of agricultural practices.
Keywords: Ecotoxicology; Environment; Fertilizers; Nanotechnology; Pesticides